The Effect Of Good Corporate Governance, Company Size, And Leverage On The Integrity Of Financial Statements - Anak Agung Putu Gede Bagus Arie Susandya; Ni Nyoman Ayu Suryandari (Al-Makki Publisher, 2023)
The Integrity of financial reports is defined as the extent to which the financial statements presented show true and honest information. Two things become the primary qualities in financial reports, namely relevance, and reliability. This study aims to empirically determine the role of good corporate governance and financial performance on the Integrity of financial statements. The variables used in corporate governance are institutional ownership, managerial ownership, and independent commissioners. Financial performance using company size and leverage. The population in this study are property and real estate companies listed on the Indonesia Stock Exchange in 2018-2021. The samples in this study were 16 property and real estate companies determined based on the purposive sampling method. The analytical tool used to test the hypothesis is multiple linear regression. The results of this study indicate that institutional ownership, managerial ownership, and firm size harm the Integrity of financial statements. The amount of institutional and managerial ownership does not make financial reports more relevant and reliable. The presence of an independent commissioner positively affects the Integrity of financial reports, and it can be considered as overseeing the process of making financial reports. While leverage does not affect the Integrity of financial statements, the low level of corporate debt cannot guarantee that financial statements are presented with high Integrity. Future research can develop this research by observing the effectiveness of the company's internal audit team. The internal audit team has an important role in the Integrity of the entity's financial statements.